Research progress of sarcopenia: Diagnostic advancements, molecular mechanisms, and therapeutic strategies - Hao-lin Wang; Long-long Liu; Ze-yu Tan; Yuan Zhou; Jing Zhang; Lin Zhai; Qian Xie; Rong-hua Liu (Experimental and Molecular Pathology)
Muscle atrophy or loss is an important sign of human aging. As the aging society approaches and human lifespan prolongs, sarcopenia has emerged as one of the significant risks influencing the quality of life of the elderly. Sarcopenia is a progressive geriatric syndrome characterized by the deterioration of skeletal muscle mass and function, which can result in an increased risk of falls, fractures, restricted physical activity, disability, mortality, and a remarkable escalation in the risk of cardiovascular diseases among the elderly. This work synthesizes recent advances in sarcopenia research, critically evaluating diagnostic frameworks, histopathological hallmarks, and molecular pathways driving disease progression. Additionally, we provide an in-depth analysis of evidence-based exercise and nutritional interventions, identifying key research gaps. These insights offer valuable references for future research on sarcopenia and clinical management, as well as lifestyle interventions such as exercise and nutrition.